2022
DOI: 10.1149/10701.0747ecst
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of MnO2 Nanoparticles Using Momordica Charantia Leaf Extract

Abstract: In this present study, an easy, eco-friendly, and efficient method for the biogenesis of manganese dioxide nanoparticles (MnO2 NPs) using Momordica charantia leaf extract is discussed. The MnO2 NPs were synthesised by reduction of potassium permanganate using Momordica charantia leaf extract as a reducing agent. Fourier-transform infrared spectra exposed the contribution of the biomolecules in the Momordica charantia leaf extract for the formation of MnO2 NPs. The UV–visible spectrum of the biosynthesized MnO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Various studies have demonstrated that M charantia contains a variety of bioactive substances, including triterpenes, alkaloids, steroids, phenols, etc 18 The phenolic component of M charantia fruit extract, which is known to have a strong reducing capacity, can be used to hypothesize and explain the process of CuO NPs production. 19 David et al 20 reported that M charantia fruit extracts were used in the green synthesis of copper nanoparticles, and their anti-microbial effectiveness was assessed. M charantia leaf extract was used as a convenient and environmentally friendly method to decrease Cu 2+ ions in the copper sulfate solution, resulting in the production of CuO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that M charantia contains a variety of bioactive substances, including triterpenes, alkaloids, steroids, phenols, etc 18 The phenolic component of M charantia fruit extract, which is known to have a strong reducing capacity, can be used to hypothesize and explain the process of CuO NPs production. 19 David et al 20 reported that M charantia fruit extracts were used in the green synthesis of copper nanoparticles, and their anti-microbial effectiveness was assessed. M charantia leaf extract was used as a convenient and environmentally friendly method to decrease Cu 2+ ions in the copper sulfate solution, resulting in the production of CuO NPs.…”
Section: Discussionmentioning
confidence: 99%
“…As such, yeast, fungi, bacteria, algae, and plant extracts are favored as reducing agents over toxic chemicals for the preparation of metal and metal oxide nanoparticles [38]. Biosynthesis not only refines the size and morphology of nanoparticles but is also more eco-friendly compared to other physicochemical methods [39]. Biological sources, particularly plant extracts, impart stabilizing and capping effects to the synthesized nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…As such, yeast, fungi, bacteria, algae, and plant extracts are favored as reducing agents over toxic chemicals for the preparation of metal and metal oxide nanoparticles [44]. Biosynthesis not only refines the size and morphology of nanoparticles but is also more eco-friendly compared to other physicochemical methods [45]. Biological sources, particularly plant extracts, impart stabilizing and capping effects to the synthesized nanoparticles.…”
Section: Introductionmentioning
confidence: 99%